PELAKSANAAN DANA KREDIT USAHA RAKYAT (KUR) PERSPEKTIF HUKUM ISLAM - Elman Johari (STIESNU Bengkulu, 2019)
Abstract Islam is a pioneering guide to happiness, Islam is not a rigid religion but a living religion to celebrate its followers and to remove its wings around the earth of God with the motto rahmatan lil alamin. Islam also stresses that in muamalah activities must not harm others and forbid eating property that is obtained in a way that is not lawful. One effort to develop and improve the economy or prosperity of the community is the existence of people's business credit institutions. This discussion uses a descriptive method that is to describe the situation or phenomenon of credit in general for KUR funds in BRI. The inductive method is to begin by expressing the specific reality of the results of the research and then consult with Islamic legal theory relating to the problem of usury so that conclusions are found. for the problem. This discussion can be concluded that the custom that prevails in the implementation of people's business loans in the existence of additional payments determined by the legal entity that carries out the credit given the term